The Revival of Classical Wisdom: Implementing Mixed Learning Approach Based on Ibnu Khaldun's Theory in Pesantren - Asysyauqi, Muhammad Farid; Riyadi, Ali; Jauhari, Moh Irmawan (JURNAL ISLAM NUSANTARA, 2024)
This study explores applying Ibn Khaldun's mixed learning concept to improving learning outcomes in Islamic boarding schools. The study used a qualitative approach through interviews, observations, and documentation, which were then analyzed using the Optimal Matching Analysis (OMA) method. The study results showed that cognitive learning concepts, such as concept learning, understanding, problem-solving, logic, and public speaking, developed significantly through the fat al-listen constructivism-based forum. Learning outcomes are not only limited to understanding but also include analysis, even to the creation stage. The class discussion forum becomes a stepping stone for students to face more significant challenges outside the classroom. The four Fatq al-Lisan constructivism-based forums ala Ibn Khaldun positively impact the development of linguistic, logic, and interpersonal skills, which are part of multiple intelligences. These findings have implications for the development of 21st-century skills, where students are not only required to master higher-order thinking skills (HOTS) collaboratively but also support linguistic, logical, and interpersonal skills.